Consumption, wealth and business cycles in Germany - Britta Hamburg; Mathias Hoffmann; Joachim Keller (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper studies the long-run relationship between consumption, asset wealth and income in Germany, based on data from 1980 to 2003. While earlier studies – mostly for the Anglo- Saxon economies – have generally documented that departures of these three variables from their common trend signal changes in asset prices, we find that for Germany they predict changes in income. Asset price changes are found to have virtually no effect on consumption – both in the short as well as in the long-run. We offer an explanation of this finding that emphasizes differences between the bank-based German financial system and the rather market-based Anglo-American system: stock ownership by private households is much less widespread in Germany than in the Anglo-Saxon economies and the share of publicly traded equity in household wealth is much smaller in Germany than in the U.S., the UK or Australia.
Keywords: G12; E44; E32; E21; G20; 330; wealth effect on consumption; business cycles; monetary policy transmission; financial systems; asset price predictability; Gesamtwirtschaftlicher Konsum; Vermögenszuwachs; Einkommenshypothese; Konjunktur; Bankensystem; Schätzung; Deutschland